Preparation method of 3D printing polymer filter plate raw material

The raw materials for polymer filter plates are prepared through 3D printing technology and step-by-step mixed melting blending method, which solves the problems of long production cycle, large energy consumption and limited varieties in the traditional production process, and achieves high-performance, high-density and high-efficiency polymer filter plate production.

CN119840034APending Publication Date: 2025-04-18SHANGHAI SUPERHIGH ENVIRONMENTAL PROTECTION TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510224655.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The production process of traditional polymer filter plates requires molds and sintering processes, resulting in long production cycles, large energy consumption, and limited varieties, which cannot meet the demand for high-quality development of high-performance polymer filter materials.

Method used

The raw materials of polymer filter plates are prepared by 3D printing technology. Through step-by-step mixed and melt blending, combined with ultra-high molecular weight polyethylene, polytetrafluoroethylene, nano-silica and other materials, composite powder particles are formed to 3D-print polymer filter plates.

Benefits of technology

The production of polymer filter plates without molds, sintering, pollution-free and energy-saving consumption is achieved, and the compactness, mechanical properties and hydrophilicity of the materials are improved, and the demand for high-quality development of high-performance filter materials is met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119840034A_ABST
    Figure CN119840034A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a 3D printing polymer filter plate raw material, and relates to the technical field of polymer sintered filter materials, the preparation method comprises the following steps: selecting a first powder group and a second powder group; heating, stirring and fusing the first powder group; heating, stirring and fusing the cooled fused mixture I and the second powder group to obtain a fused mixture II; the obtained fused mixture II is put into a pressurization system with a heating charging barrel to be subjected to extrusion fusion forming treatment through a hot melting transfer method, alloy plastic is obtained, and the alloy plastic is crushed and ground into powder; heating, stirring and fusing the obtained powder and the first powder group, cooling and sieving to obtain powder particles; and the obtained powder particles are subjected to deburring treatment, the powder particles obtained through sieving are the raw material of the 3D printing polymer filter plate, and compared with a traditional manufacturing mode of the polymer filter plate, the raw material prepared through the method can be directly used for 3D printing of the polymer filter plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer sintered filter materials, and in particular to a method for preparing a raw material for a 3D printed polymer filter plate. Background Art

[0002] In recent years, with the continuous advancement of new quality productivity and high-quality development, the development of high-purity extraction and separation technology of lithium batteries and hydrogen energy storage materials in the new energy industry and laser smoke filtration and inert gas push in the additive industry all require high-quality and high-precision personalized filter materials. This has put forward new requirements for technicians in the polymer sintered filter material industry. It is also an urgent problem to be solved in the field of environmental protection materials today to develop a high-quality, high-performance filter material that does not require molds, sintering, pollution-free, and saves a lot of energy consumption (heating electricity and cooling water), and has a rich variety and accelerated iteration of polymer filter plates to meet the development needs of new quality productivity.

[0003] Traditional polymer filter plates need to be opened with corresponding molds of corresponding sizes. When opening the mold, the material surface must be precise and smooth, which results in a long mold production cycle. It cannot adapt to the innovative iteration of polymer filter plates and the personalized needs of emerging industries, and inhibits the urgent demand for high-quality and clean space filter materials brought about by the development of new productivity. In the specific production, the mold needs to be placed in a heating furnace for heating and sintering, and enter the cooling section through a constant temperature process. After opening the furnace door, spray cooling is performed, and then the semi-finished filter plate is taken out after the mold is opened. The filter plate needs to be processed from head to tail, and then cut, glued, fixed and bolted to become a finished filter plate. The period fully reflects that the production cycle is too long, the process requirements are extremely high, the process is cumbersome, the energy consumption is high, and the variety and specifications are limited by the mold, which results in serious restrictions on the variety of filter plates, and is not conducive to green, low-carbon and carbon-reducing production methods.

[0004] Therefore, a new type of polymer filter plate that does not require molds, does not require sintering, is pollution-free, and saves a lot of energy consumption, that is, a polymer filter plate made by 3D printing technology, can be used to solve the urgent demand for high-performance polymer filter materials in high-quality development. However, 3D printing technology has certain requirements for its raw materials when making polymer filter plates. In this regard, the present invention proposes a method for preparing raw materials for 3D printed polymer filter plates. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention aims to propose a method for preparing a raw material for a 3D printed polymer filter plate. The specific scheme is as follows:

[0006] A method for preparing a raw material for a 3D printed polymer filter plate, the method comprising the following steps:

[0007] S1: Selecting a first powder group including ultra-high molecular weight polyethylene powder, high-density polyethylene powder, and polytetrafluoroethylene powder, and selecting a second powder group including nano silicon dioxide powder, diatomaceous earth powder, nano antioxidant, and nano silicate;

[0008] S2: heating the first powder group in step S1, stirring and fusing it until the temperature reaches 130° C., and then the stirring is finished to obtain a fused mixture 1, which is cooled and set aside;

[0009] S3: heating and stirring the cooled partially fused mixture 1 obtained in step S2 and the second powder group in step S1 until the temperature reaches 150° C. and stirring is terminated, and the mixture is cooled and set aside to obtain a fused mixture 2;

[0010] S4: placing the fused mixture obtained in step S3 into a pressurized system with a heated barrel for hot melt transfer extrusion fusion molding to obtain an alloy plastic, and crushing and grinding the alloy plastic into powder, cooling it for later use;

[0011] S5: heating the powder obtained in step S4 and the remaining fused mixture in step S2, stirring and fusing them until the temperature reaches 150° C., cooling and sieving to obtain powder particles with a suitable particle size;

[0012] S6: Deburring the powder particles obtained in step S5, and the powder particles obtained by sieving are the raw materials for 3D printing polymer filter plates, and the raw materials are stored.

[0013] Furthermore, in the first powder group of step S1, the particle sizes of the ultra-high molecular weight polyethylene powder and the high-density polyethylene powder are in the micron level, and the particle size of the polytetrafluoroethylene powder is in the nanometer level.

[0014] Furthermore, in the first powder group of step S1, the mass ratio of ultra-high molecular weight polyethylene powder, high-density polyethylene powder and polytetrafluoroethylene powder is 65:30:5.

[0015] Furthermore, in step S3, the mass ratio of the fused mixture 1, nano silicon dioxide powder, diatomaceous earth powder, nano antioxidant and nano silicate is 30:4.5:3.5:3:2.

[0016] Furthermore, in step S4, the heating barrel is a double-layer structure, wherein the middle layer is a nitrogen protective layer;

[0017] The hot melt transfer method of extrusion fusion molding is specifically as follows: the third powder assembly is put into the heating barrel for heating. When the temperature rises to 235°C, the pressure device of the pressurizing system is started after keeping warm for 30 minutes. After being pressurized, the heating barrel extrude the fused mixture 2 through several discharge ports at the bottom. The extruded flat material is cooled by the cooling water flow channel to form an alloy plastic.

[0018] Furthermore, in step S5, additives are added during the heating, stirring and fusing process, and the additives include polyacrylic acid resin and stearic acid.

[0019] Furthermore, the heating, stirring and fusion processes are all achieved by a high-speed mixer, and the speed range of the high-speed mixer is between 150r / min-220r / min.

[0020] Furthermore, the specific surface area per gram of nano-silicon dioxide powder and diatomaceous earth powder is 100-300 m2;

[0021] Nano antioxidant uses nano titanium dioxide, with a specific surface area of ​​180-220㎡ per gram.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) Through this preparation method, the first powder group is first fused for the first time, cross-linked with each other, and covalently bonded to achieve a preliminary increase in hardness. Then, the first powder group is fused for the second time under the action of the second powder group. The formed composite material (i.e., fused mixture 2) changes the pore structure on the basis of increased hardness, thereby improving hydrophilicity, mechanical properties, etc. Then, the powder obtained by fused mixture 2 continues to be fused with the first powder group for the third time. This fusion is different from the previous two fusions. At this time, the polarity and compatibility of the material will be improved, and the mechanical properties of the ultra-high density polyethylene therein will be dispersed and strengthened, so that the formed powder particles will be used as the raw material for 3D printing polymer filter plates in the future. Its density and mechanical properties are close to the optimal state.

[0024] (2) The ultra-high molecular weight polyethylene powder and high-density polyethylene powder in the first powder group have low melting points and high melt indexes, while the nano-silicon dioxide powder, diatomaceous earth powder, and nano-antioxidant in the second powder group have high melting points and large density differences. Therefore, in the present invention, through the step-by-step mixing and melting of this preparation method, the first powder group and the second powder group with completely different material densities, molecular weights, particle sizes, specific surface areas, and melting points can be fused multiple times to form the raw materials for the polymer filter plate.

[0025] (3) When the raw materials prepared by the present invention are used for 3D printing of polymer filter plates, compared with the existing traditional production of polymer filter plates that rely on molds and adopt sintering process to form the production method, the microporous channels of the raw materials in the 3D printing process are regular, the morphology is fuller and the efficiency is higher, higher precision can be achieved at a lower cost, and rapid and automated manufacturing of polymer filter plates can be realized. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is an infrared spectrum of the fused mixture 1 after the first fusion of the present invention;

[0027] Figure 2 The figure is a schematic diagram of the compactness structure of the raw material of the polymer filter plate in the present invention under a high-power magnifying glass. DETAILED DESCRIPTION

[0028] The present invention will be further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0029] The present invention provides a raw material synthesis process for 3D printing polymer filter plates. The raw materials are mainly formed by components such as high-density polyethylene, polytetrafluoroethylene, and ultra-high molecular weight polyethylene. High-density polyethylene, which is an organic material with a low melting point and a high melting index, is used to perform step-by-step mixing and melting of polytetrafluoroethylene and inorganic materials such as diatomaceous earth, nano-silicon dioxide, and nano-titanium oxide, which have high melting points and large density differences, to compensate for the reduction in mechanical properties. The molten materials are made into particles and then the burrs are removed from the surface together, so that the surface of the particle material is spherical, smooth, and free of burrs, thereby forming the raw material for making the 3D printing polymer filter plate.

[0030] The raw material of the present invention can make the microporous channels regular, the morphology full and the efficiency higher when 3D printing the polymer filter plate, achieve higher precision at a lower cost, realize rapid automated manufacturing, meet the requirements of stable use in various corrosion-resistant, photocatalytic, high-cleanliness and arc flue gas environments, and have the characteristics of long service life.

[0031] In addition, compared with the traditional production method of polymer filter plates that relies on molds and uses sintering technology to form them, the production method of 3D printed polymer filter plates can achieve green, energy-saving and carbon-free production. It can also enable the varieties and categories of polymer filter materials to be flexibly designed and personalized according to actual needs, fully broadening the use scenarios and application environments of polymer filter materials. By modifying the polymer materials, it can also enable them to work stably in various corrosion-resistant, photocatalytic, high-cleanliness and arc flue gas environments, while extending the service life of the filter materials.

[0032] In this regard, the present invention proposes a method for preparing raw materials for 3D printing polymer filter plates, which is essentially a step-by-step mixing and melting blending method, that is, the selected materials are mixed and melted in a step-by-step manner, and after different fusions, the performance of the materials is correspondingly improved, and finally a balance is achieved to form the aforementioned raw materials. This preparation method includes steps S1-S6. Specifically, it includes the following steps:

[0033] S1: Selecting a first powder group including ultra-high molecular weight polyethylene powder, high-density polyethylene powder, and polytetrafluoroethylene powder, and selecting a second powder group including nano silicon dioxide powder, diatomaceous earth powder, nano antioxidant, and nano silicate;

[0034] It should be noted that in the first powder group in step S1, the particle size of the ultra-high molecular weight polyethylene powder is micron-level, such as 10-15 microns; the particle size of the high-density polyethylene powder is micron-level, such as 40-50 microns; the particle size of the polytetrafluoroethylene powder is nanometer-level, such as 1000-1200 nanometers; the mass ratio of the ultra-high molecular weight polyethylene powder, the high-density polyethylene powder, and the polytetrafluoroethylene powder is 65:30:5. In the second powder group in step S1, the particle size of the nano-silicon dioxide powder is 20-40 nanometers; the particle size of the diatomaceous earth powder is 4-5 microns; the nano-antioxidant uses nano-titanium dioxide, and the particle size of the nano-titanium dioxide is 20-25 nanometers; the nano-silicate uses nano-sodium silicate, and the particle size is 500-700 nanometers.

[0035] After the selection of materials is completed, the first fusion of step S2 is entered. S2: the first powder group in step S1 is heated, stirred and fused until the temperature reaches 130°C and the stirring is ended to obtain a fused mixture 1, which is cooled and set aside;

[0036] It should be noted that in step S2, the first fusion of the components in the first powder group is carried out by stirring and fusion treatment at a high temperature. Specifically, ultra-high density polyethylene powder, high-density polyethylene powder and polytetrafluoroethylene are placed in a high-speed mixer, which is operated at a speed of 200 r / min. The stirring is ended when the friction temperature of the barrel rises to 130°C to obtain a fused mixture, which is then bagged for later use after cooling.

[0037] Since ultra-high molecular weight polyethylene powder is selected as the main raw material in the first fusion, high-density polyethylene powder and polytetrafluoroethylene powder (nanoscale) are added to the ultra-high molecular weight polyethylene powder for cross-linking treatment, and the gradient layering method from the surface to the bulk phase is used to regulate the "rigidity" of the PTFE (polytetrafluoroethylene) / HDPE (high-density polyethylene) composite-UHMEPE (ultra-high molecular weight polyethylene) particles to construct a reasonable "bridging" middle layer. The hardness of the plastic is improved by the "covalent" effect of the melt, which can improve the close combination of the double bonds of the organic framework middle layer composite HDPE and the double bonds of the bulk UHMEPE, and give play to the covalent bond between the polytetrafluoroethylene nanocrystals and the polymer matrix, so that the material can better resist deformation when subjected to external forces and show higher hardness. The verification data is shown in ( Figure 1 ).

[0038] It should be noted that the aforementioned gradient layering method from the surface layer to the bulk phase is specifically embodied in that, compared with the crystallization of polyethylene (PE) occurring in the planar and trans conformations, the crystal structure of polytetrafluoroethylene (PTFE) in the present invention, i.e. -(CF2) n -, it is quite different, it has many crystal forms, and at temperatures well below the melting point, the molecular motion in the crystal is quite violent, at temperatures above 19°C the chains are able to undergo angular displacements, and this angular displacement increases at temperatures above 30°C until the melting point is reached, so that the covalent bond in the first fusion is achieved.

[0039] Figure 1 This is the infrared spectrum of the fusion mixture 1 after the first fusion. The infrared spectrum is an important analytical tool used to study the absorption, emission or scattering characteristics of a substance in the infrared light region. The chemical bonds or functional groups corresponding to the absorption peaks in the figure can be used to infer the chemical structure of the substance.

[0040] from Figure 1 It can be seen that the infrared spectrum shows that the CF bond after melt mixing is at wave number 1202 cm^ -1 , 1147cm^ -1There are two obvious absorption peaks, which means that the fused mixture 1 has strong absorption in the infrared light region with wave numbers of about 0.13cm and 0.12cm (i.e. 13000nm or 13μm, i.e. 12000nm or 12μm), reflecting the chemical structure convergence of the fused mixture 1. In terms of the absorption characteristics of infrared radiation, it shows that the covalent bonds between the polytetrafluoroethylene nanocrystals and the polymer matrix are intact, and the cross-linking effect of its molecular structure and chemical composition is good. After the first fusion of step S2, the second fusion of step S3 is entered. S3: The cooled partially fused mixture 1 obtained in step S2 is subjected to a heating, stirring and fusion treatment with the second powder group in step S1 until the temperature reaches 150°C and the stirring is ended. After cooling, it is used to obtain a fused mixture 2;

[0041] It should be noted that in step S3, the mass ratio of the fused mixture 1, nano silicon dioxide powder, diatomaceous earth powder, nano antioxidant and nano silicate is 30:4.5:3.5:3:2.

[0042] The fusion mixture 1, nano silicon dioxide powder, diatomite powder, nano titanium dioxide and nano sodium silicate are subjected to a heating, stirring and fusion treatment. It should be noted that, unlike the heating, stirring and fusion treatment in step S2, in step S3, the fusion materials are loaded into a high-speed mixer, which is operated at a speed of 200 r / min, and the stirring is completed when the friction temperature of the barrel rises to 150° C., to obtain the fusion mixture 2, which is then bagged for later use after cooling.

[0043] Optimally, the fused mixture 2 obtained in step S3 can be subjected to a secondary melting treatment, and the secondary melting treatment is specifically: adding nano silicon dioxide powder, diatomaceous earth powder, nano antioxidant, and nano silicate to the third powder group for melt mixing to form a fused mixture 2 as a eutectic mixture.

[0044] It should be noted that the materials selected for melting have the following requirements: Nano silicon dioxide has small size effect, surface interface effect, and quantum size effect, which make the surface area of ​​its nanoparticles larger relative to the volume, and the specific surface area per gram needs to be limited to 100-300㎡, such as 250㎡; The specific surface area per gram of nano diatomaceous earth needs to be limited to 100-300㎡, such as 250㎡, which can lead to stronger interaction between surface atoms and molecules and the surrounding environment, and increase surface energy and reaction activity; Nano titanium dioxide has anti-ultraviolet, antibacterial, self-cleaning, and anti-aging properties, and at the same time, the specific surface area per gram needs to be limited to 180-220㎡, about 200㎡; Nano silicate is to improve the melting index of the material, can be separated and dissolved by boiling in water, and can increase the micropore opening rate. The specific surface area per gram is not limited.

[0045] In this way, the eutectic blend obtained after the secondary melt treatment can form a printable composite material. This composite material is a composite material of silica nanopowder and titanium dioxide antioxidant powder dispersed in a polyethylene matrix and polytetrafluoroethylene, showing excellent performance improvements, including mechanical properties, thermal stability and anti-pollution ability.

[0046] After the second fusion in step S3, the third fusion in step S4 is performed. S4: the fused mixture obtained in step S3 is placed in a pressurized system with a heated barrel for hot melt transfer extrusion fusion molding to obtain an alloy plastic, and the alloy plastic is crushed and ground into powder, cooled and set aside.

[0047] It should be noted that the third fusion in step S4 is performed by hot melt transfer extrusion fusion. Since the ultra-high molecular weight polyethylene in the fusion mixture 2 has a low melt index, the selected melt index is usually selected between 0.1-0.4g / 10min in the present invention. This is because the larger the molecular weight, the lower the melt index, the greater the apparent viscosity of the melt, and the poor fluidity. The general extruder cannot extrude it, and can only use a pressurized system with a heating barrel that can be raised and lowered for hot melt transfer extrusion fusion molding. Among them, the heating barrel is double-layered, and the middle layer of the heating barrel is a nitrogen protective layer to prevent the material in the heating barrel from being oxidized when the material is heated, heated, and kept warm.

[0048] The specific operation of hot melt transfer extrusion fusion molding is: the fused and cooled fusion mixture is loaded into the heating barrel for heating. When the temperature rises to 235°C and is kept warm for 30 minutes, the material in the heating barrel begins to melt. At this time, the pressure device of the pressurization system is started. After being pressurized, the heating barrel forces the material out of the heating barrel through several outlets at the bottom.

[0049] The outlet of the heating barrel is flat (10 mm in width and 3 mm in thickness). The forced extruded flat material is cooled by the cooling water channel to form an alloy plastic strip, which is rolled into a disc at the end to complete the hot melt extrusion fusion coil of "alloy plastic". The coil is then cut, crushed, ground into powder, cooled and bagged for later use.

[0050] After the third fusion in step S4, the fourth fusion in step S5 is entered. S5: the powder obtained in step S4 and the remaining fusion mixture in step S2 are loaded into a mixer for heating, stirring and fusion treatment until the temperature reaches 150°C and the stirring is ended. After cooling, the powder particles with the required particle size are sieved.

[0051] It should be noted that in step S5, the first powder group and the powder are melt-mixed. The principle is to modify the powder surface of the powder (the powder is a hard particle) of the polyacrylic acid resin with a mass ratio of 0.5%, the stearic acid auxiliary material with a mass ratio of 0.5% and the alloy plastic powder through the "post-modification" strategy, reduce the polarity of the material, and use the ultra-fine treatment method to improve the compatibility of the additive with the alloy plastic and ultra-high density polyethylene, and disperse and strengthen the mechanical properties of the ultra-high density polyethylene. The specific operation of the ultra-fine treatment method is to load the above-mentioned materials to be fused into a high-speed mixer, run at a speed of 160r / min, wait until the friction temperature of the barrel rises to 150°C, and then end the stirring, and then sieve and extract the materials that meet the particle size after cooling to obtain powder particles with the particle size meeting the requirements.

[0052] The polyacrylic acid added in the "post-modification" contains super-hydrophilic groups, which undergo grafting reaction with the surface of high-density polyethylene treated with low-temperature plasma, so that some micro-phase separation structures are formed inside the material, thereby increasing the porosity and improving the relative super-hydrophilicity of high-density polyethylene materials;

[0053] Finally, step S6 is performed: the powder particles obtained in step S5 are deburred, and the powder particles obtained by sieving are the raw materials for 3D printing polymer filter plates, and the raw materials are stored.

[0054] It should be noted that the deburring process in the present invention is to select dry ice with a temperature of -78.5°C and a particle size of 3mm, and spray it out of the muzzle at a speed of 3 cubic meters per minute. The essence of the deburring process is to use dry ice particles as a medium for dispersion enhancement and burr removal. Through the characteristics of dry ice sublimation after spraying, a high-speed detachment effect is produced, thereby instantly crushing and removing the burrs on the surface of the particles, and further enhancing the hardness of the powder particles. At the same time, when the dry ice particles impact the surface of the powder, their momentum disappears instantly, and they are immediately vaporized, and their volume expands 800 times instantly, forming a micro-explosion, blowing away the dirt or burrs on the surface of the powder, making the powder spherical, complete, smooth and hard. At the same time, since dry ice does not leave any residue when it evaporates, and does not form liquid, it avoids the trouble of cleaning up the residue and also reduces the risk of secondary pollution.

[0055] After the deburring process is completed, the material is screened, (8) the dispersion strengthened and deburred material is screened, and the composite material that meets the particle size is bagged for use. The composite material can be set to a particle size of 10 microns, and the residual material that does not meet the particle size is used to manufacture the wear-resistant plate, which plays a role in recycling and environmentally friendly green low-carbon production.

[0056] In summary, the present invention also proposes the following embodiments:

[0057] The materials used in the examples are shown in Table 1.

[0058] Table 1

[0059]

[0060] S1: A first powder group including 15 micron ultra-high molecular weight polyethylene powder, 42 micron high-density polyethylene powder, and 1000 nanometer polytetrafluoroethylene powder is selected, and the mass ratios of the three are 63%, 35%, and 2% respectively, and a second powder group including 30 nanometer nano-silicon dioxide powder, 45 micrometer diatomaceous earth powder, 21 nanometer nano-antioxidant, and 600 nanometer nano-silicate is selected. The ultra-high density polyethylene powder adopts Ticona brand: GUR4022, the high-density polyethylene powder adopts Daehan Petrochemical brand: X04, the polytetrafluoroethylene powder adopts DuPont PTFE, brand MP1200, the nano-silicon dioxide powder adopts Henan Haiborui Silicon Material Technology Co., Ltd., brand NPS-L nano-silicon dioxide, the nano-antioxidant adopts nano-titanium dioxide, and the nano-silicate adopts Tianjin Zhiyuan Chemical Sun brand nano-sodium silicate.

[0061] In this embodiment, the melting points of the ultra-high density polyethylene powder and the high-density polyethylene powder are both between 125°C and 135°C. The difference between them is that the ultra-high density polyethylene does not flow after melting, while the high-density polyethylene powder flows after reaching the melting point, and the polytetrafluoroethylene material is wrapped in the process of flowing, forming a molten mixture in a local sense (the mixture is treated under low-temperature plasma conditions);

[0062] When high-density polyethylene and tetrafluoroethylene are placed in a low-temperature plasma environment, these active free radicals can interact with the molecules of high-density polyethylene and tetrafluoroethylene, and cause hydrogen atoms on the molecular chains to undergo hydrogen abstraction reactions, thereby initiating cross-linking of the molecular chains and activating atoms or groups on the surface of the molecules, thereby initiating a chemical reaction between the two and forming new covalent bonds.

[0063] S2: 63% by mass of ultra-high density polyethylene powder, 35% by mass of high density polyethylene powder, and 2% by mass of polytetrafluoroethylene are placed in a high-speed mixer, and the mixer is operated at a speed of 200 r / min. The mixing is stopped when the friction temperature of the barrel rises to 130°C to obtain a fused mixture 1, which is then bagged for later use after cooling;

[0064] S3: Take 30 parts by weight of fusion mixture 1, add 4.5 parts by weight of nano silicon dioxide powder, 3.5 parts by weight of diatomaceous earth powder, 3 parts by weight of nano titanium dioxide and 2 parts by weight of nano sodium silicate, and perform heating, stirring and fusing treatment. Specifically, the fusion materials are loaded into a high-speed mixer, and the mixer is operated at a speed of 200 r / min. When the friction temperature of the barrel rises to 150° C., the stirring is terminated to obtain fusion mixture 2, and the fusion mixture 2 as a eutectic mixture is formed and then cooled and bagged for later use;

[0065] S4: putting the fused mixture 2 obtained in step S3 into a pressurizing system with a heating barrel for hot melt transfer extrusion fusion molding treatment, specifically, putting the fused mixture 2 that has been cooled after fusion into the heating barrel for heating. When the temperature rises to 235°C and is kept warm for 30 minutes, the material in the heating barrel begins to melt. At this time, the pressure device of the pressurizing system is started and the pressure is set to 5 MPa. After being pressurized, the heating barrel forces the material to be squeezed out of the heating barrel through several discharge ports at the bottom to obtain an alloy plastic, and the alloy plastic is crushed and ground into powder, cooled and set aside.

[0066] S5: The powder obtained in step S4 is blended with the remaining powder in step S2 at a mass ratio of 70%, and the mixture is loaded into a mixer for heating, stirring and blending treatment. The specific operation is to load the above materials to be fused into a high-speed mixer, run the mixer at a speed of 160r / min, and end the stirring when the friction temperature of the barrel rises to 150°C. Then, the materials that meet the particle size are sieved after cooling to obtain powder particles that meet the particle size.

[0067] S6: Deburring the powder particles obtained in step S5, and the powder particles obtained by sieving are the raw materials for 3D printing polymer filter plates.

[0068] It should be noted that, in summary, the raw material of the 3D printed polymer filter plate completed in this embodiment, that is, the composite powder particles, has a particle size of about 5 microns, and the particle shape is spherical, which can be smoothly sprayed out by the 3D printing nozzle, and a high degree of uniformity is achieved in the powder spreading and powder feeding links of the printing process. The dense structure diagram under a high-power magnifying glass is shown in FIG. Figure 2 ,like Figure 2 As shown, the pore structure of high-density polyethylene materials is changed, thereby improving the relative super-hydrophilicity of high-density polyethylene materials. It comprehensively ensures that the density and mechanical properties of printed products are in the best state, and at the same time has the characteristics of green and low carbon, high control precision, and long service life. In particular, it has unmanned and automated production functions, which promotes the digital transformation and high-quality development of enterprises.

[0069] The traditional material formula is relatively simple. For example, the sintered material formed by ultra-high density polyethylene and high-density polyethylene is not modified. The molding method is to put the mixed material into a mold and sinter it.

[0070] Through the "post-modification" strategy, the powder surface of 0.5% polyacrylic acid resin, 0.5% stearic acid auxiliary material and alloy plastic powder (the powder is hard particles) is modified, the purpose of which is to increase the porosity and improve the relative super hydrophilicity of high-density polyethylene materials.

[0071] Based on the raw materials obtained in the above embodiments, the present invention carried out actual 3D printing operations, and the performance tests of the obtained polymer filter plate and the polymer filter plate obtained by the traditional production method are shown in the following Table 2 and Table 3 respectively.

[0072] Table 2

[0073]

[0074]

[0075] From the data in Table 2, it can be seen that the tensile strength, elongation at break, impact strength and bending strength of the polymer filter plate prepared by the present invention are better than the index requirements, and the elongation at break is significantly better than the index requirements, indicating that the mechanical properties of the raw materials of the polymer filter plate of the present invention have been improved. At the same time, the Vicat heat resistance of the polymer filter plate is also significantly better than the index requirements, indicating that the thermal stability performance has also been improved. In addition, the dust removal rate of the polymer filter plate is also better than the index requirements, indicating that the anti-pollution ability has also been improved.

[0076] Table 3

[0077]

[0078] From the data in Table 3, it can be seen that most of the performance test indicators of the polymer filter plate prepared by the traditional method are slightly better than the index requirements, indicating that although the polymer filter plate that requires raw materials and molds to be produced has undergone mold opening procedures, high-demand processes, and cumbersome processes, its performance has not been improved to a great extent. It also requires sintering and energy consumption, and it is difficult to solve the urgent demand for high-performance polymer filtration materials in high-quality development.

[0079] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a raw material for a 3D printed polymer filter plate, characterized in that: The preparation method comprises the following steps: S1: Selecting a first powder group including ultra-high molecular weight polyethylene powder, high-density polyethylene powder, and polytetrafluoroethylene powder, and selecting a second powder group including nano silicon dioxide powder, diatomaceous earth powder, nano antioxidant, and nano silicate; S2: heating the first powder group in step S1, stirring and fusing it until the temperature reaches 130° C., and then the stirring is finished to obtain a fused mixture 1, which is cooled and set aside; S3: heating and stirring the cooled partially fused mixture 1 obtained in step S2 and the second powder group in step S1 until the temperature reaches 150° C. and stirring is terminated, and the mixture is cooled and set aside to obtain a fused mixture 2; S4: placing the fused mixture obtained in step S3 into a pressurized system with a heated barrel for hot melt transfer extrusion fusion molding to obtain an alloy plastic, and crushing and grinding the alloy plastic into powder, cooling it for later use; S5: heating the powder obtained in step S4 and the remaining fused mixture in step S2, stirring and fusing them until the temperature reaches 150° C., cooling and sieving to obtain powder particles with a suitable particle size; S6: Deburring the powder particles obtained in step S5, and the powder particles obtained by sieving are the raw materials for 3D printing polymer filter plates, and the raw materials are stored.

2. The method for preparing a 3D printed polymer filter plate raw material according to claim 1, characterized in that: In the first powder group of step S1, the particle sizes of the ultra-high molecular weight polyethylene powder and the high-density polyethylene powder are in the micron level, and the particle size of the polytetrafluoroethylene powder is in the nanometer level.

3. The method for preparing a 3D printed polymer filter plate raw material according to claim 1, characterized in that: In the first powder group in step S1, the mass ratio of ultra-high molecular weight polyethylene powder, high-density polyethylene powder and polytetrafluoroethylene powder is 65:30:

5.

4. The method for preparing a 3D printed polymer filter plate raw material according to claim 1, characterized in that: In step S3, the mass ratio of the fused mixture 1, nano silicon dioxide powder, diatomaceous earth powder, nano antioxidant and nano silicate is 30:4.5:3.5:3:

2.

5. The method for preparing a 3D printing polymer filter plate raw material according to claim 1, characterized in that: In step S4, the heating barrel is a double-layer structure, wherein the middle layer is a nitrogen protective layer; The hot melt transfer method of extrusion fusion molding is specifically as follows: the third powder assembly is put into the heating barrel for heating. When the temperature rises to 235°C, the pressure device of the pressurizing system is started after keeping warm for 30 minutes. After being pressurized, the heating barrel extrude the fused mixture 2 through several discharge ports at the bottom. The extruded flat material is cooled by the cooling water flow channel to form an alloy plastic.

6. The method for preparing a 3D printing polymer filter plate raw material according to claim 1, characterized in that: In step S5, additives are added during the heating, stirring and fusing process, and the additives include polyacrylic acid resin and stearic acid.

7. The method for preparing a 3D printing polymer filter plate raw material according to claim 1, characterized in that: The heating, stirring and fusion processes are all achieved by a high-speed mixer, and the speed range of the high-speed mixer is between 150r / min and 220r / min.

8. The method for preparing a 3D printing polymer filter plate raw material according to claim 1, characterized in that: The specific surface area per gram of nano-silicon dioxide powder and diatomaceous earth powder is 100-300㎡; Nano antioxidant uses nano titanium dioxide, with a specific surface area of ​​180-220㎡ per gram.